Legal Risks Faced by Auditors: Liability for Errors in Audit Opinions - Widiarti, Pipit Angelia (Advances in Managerial Auditing Research, 2025)
Purpose: This study explores the legal risks auditors face, focusing on the interplay between stakeholder expectations, evolving regulatory frameworks, and behavioral implications. It examines how these factors influence auditor liability, independence, and professional decision-making, offering insights into mitigating legal risks and improving audit quality. Research Design and Methodology: Using a qualitative approach, this study employs a systematic literature review (SLR) to analyze prior research on auditor liability, stakeholder expectations, and regulatory dynamics. The study synthesizes findings from academic journals, regulatory reports, and professional standards to develop a multidimensional framework for understanding auditor legal risks. Findings and Discussion: The findings reveal that misaligned stakeholder expectations significantly increase litigation risks for auditors, as many stakeholders view audit opinions as guarantees rather than reasonable assurance. Regulatory frameworks, such as the Sarbanes-Oxley Act and International Standards on Auditing, amplify auditors’ legal exposure due to varying compliance demands across jurisdictions. Additionally, behavioral implications, including increased auditor conservatism, are key consequences of litigation fears, which may compromise audit quality. This study also highlights the role of audit committees and professional training in mitigating these risks. Implications: The research provides practical and managerial insights, emphasizing the need for enhanced training programs to address stakeholder expectations and litigation risks. It advocates for stronger independent oversight through audit committees and refining audit standards to clarify the scope of audit opinions. These findings offer valuable contributions to academia and practice, supporting efforts to reduce legal risks while maintaining audit integrity.